Epidemiological survey of acute low-tone sensorineural hearing loss. (10th March 2017) - Sato, Hiroaki; Kuwashima, Shigeru; Nishio, Shin-ya; Kitoh, Ryosuke; Fukuda, Satoshi; Hara, Akira; Hato, Naohito; Ikezono, Tetsuo; Ishikawa, Kotaro; Iwasaki, Satoshi; Kaga, Kimitaka; Matsubara, Atsushi; et al.
Abstract: Objectives: A nationwide epidemiological survey involving 23 hospitals in Japan was conducted and the predictive values of demographic data were examined statistically. Methods: A total of 642 patients from 23 hospitals, including 20 university hospitals, in Japan were enrolled in the study. Age ranged from 8 to 87 years, and all were diagnosed with acute low-tone sensorineural hearing loss (ALHL) between 1994 and 2016. Demographic data for the patients, such as symptoms, gender, mean age, and distribution of ALHL grading, were collected and analyzed in relation to prognosis using Student's t -test, χ 2 test and logistic regression. Results: Female gender ( p  < .013), younger age ( p  < .001), low-grade hearing loss ( p  < .001), and shorter interval between onset and initial visit ( p  < .004) were significantly predictive of a good prognosis. The prognosis for definite ALHL was significantly better than that for probable ALHL ( p  < .007). Conclusions: The severity of initial hearing loss, interval between onset and initial visit and age were important prognostic indicators for ALHL, while female gender was an important prognostic indicator peculiar to ALHL.